Sekolah Perempuan Teras Harmoni : Upaya Peningkatan Kesejahteraan Keluarga di Desa Ketapang - Annisa Mellani Jauzaa; Septiana Hanum Annisyafa; Sifa Aura Amalia Nugraha (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Ketapang Village is located in Susukan sub-district, Semarang Regency. The Teras Harmoni Women's School program, based on an ecological mental health model, has successfully empowered women in Ketapang Village. The village faces challenges such as the low participation of women in the labor force, with 380 (22%) and the lack of access to higher education with 99 (6%) female graduates. Facing these challenges, Sekolah Perempuan Teras Harmoni comes as an innovative initiative to empower women, aiming to improve family welfare through a holistic approach encompassing education, mental health, economic development, and improved managerial skills. The Sekolah Perempuan Teras Harmoni approach is based on an ecological mental health model, integrating various systems to build family and community well-being. This model, referring to Urie Bronfenbrenner's concept, considers the interaction between individuals and their environment at various levels. There is an increase in the capacity of student organizations supporting the implementation of PPK Ormawa. The increased capacity of student organizations in the implementation of PPK Ormawa can be seen from the role played by students in assisting and managing various programs, especially at Teras Harmoni Women's School. Proven by the Wilcoxon Test with the results (.000). which can be interpreted that there is an increase in the PPK Ormawa Team. And the increase in students or participants of the Teras Harmoni Women's School is evidenced by the Paired sample t-test on each program with (.000) which means that the dedication of the PPK ORMAWA HIMA BK Team has a significant and positive impact.